The new Italian Republic : from the fall of the Berlin Wall to Berlusconi - Gundle, Stephen, 1956-; Parker, Simon, 1964- (London ; New York : Routledge, 1996)
The New Italian Republic charts the breakdown of the old party system and examines the changed political climate that has allowed Berlusconi to rise as Italy's new master and subsequently precipitated his rapid fall from power.
Chapter Introduction: the new Italian Republic / Stephen Gundle -- part Part I Context -- chapter 1 Explaining Italy's crisis / Paul Ginsborg -- chapter 2 Electoral reform and political change in Italy, 1991-1994 / Simon Parker -- part Part II The old party system -- chapter 3 Political Catholicism and the strange death of the Christian Democrats / Paul Furlong -- chapter 4 Italian Communism in the First Republic / Stephen Hellman -- chapter 5 The rise and fall of Craxi's Socialist Party / Stephen Gundle -- chapter 6 The fate of the secular Centre -- Mark Donovan / The Liberals, Republicans and Social Democrats -- part Part III The 'new' parties -- chapter 7 The Northern League -- Ilvo Diamanti / From regional party to party of government -- chapter 8 Forza Italia: the new politics and old values of a changing Italy -- Patrick McCarthy / The new politics and old values of a changing Italy -- chapter 9 Towards a modern Right -- Alleanza Nazionale and the 'Italian Revolution' / Carlo Ruzza -- chapter 10 The great failure? -- Martin J. Bull / The Democratic Party of the Left in Italy's transition -- chapter 11 The 'Left Opposition' and the crisis: Rifondazione Comunista -- John M. Foot / Rifondazione Comunista -- part Part IV Politics and society -- chapter 12 A legal revolution? -- David Nelken / The judges and Tangentopoli -- chapter 13 The mass media and the political crisis / Stephen Gundle and Noëlleanne O'Sullivan -- chapter 14 The system of corrupt exchange in local government / Donatella della Porta -- chapter 15 The resistible rise of the new Neapolitan Camorra / Percy Allum -- chapter 16 The changing Mezzogiorno -- Salvatore Lupo / Between representations and reality -- part Part V Economic aspects of the crisis -- chapter 17 The economic elites and the political system / Alan Friedman -- chapter 18 Excesses and limits of the public sector in the Italian economy -- Fiorella Padoa Schioppa Kostoris / The ongoing reform -- chapter 19 Industrial relations and the labour movement / Mimmo Carrieri -- part Part VI Conclusion -- chapter 20 Italian political reform in comparative perspective / David Hine.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Italy -- Politics and government -- 1994-2018.; Italy -- Politics and government -- 1976-1994.; Democracy -- Italy; Political parties -- Italy; Judicial power -- Italy; Italie -- Politique et gouvernement -- 1994-2018.; Italie -- Politique et gouvernement -- 1976-1994.; Pouvoir judiciaire -- Italie; POLITICAL SCIENCE -- Civics & Citizenship; Democracy; Judicial power; Political parties; Politics and government; Italy; 1976-2018; Politics; Italy